Effect of the annealing on the power factor of un-doped cold-pressed SnSe. (25th January 2017) - Morales Ferreiro, J.O.; Diaz-Droguett, D.E.; Celentano, D.; Reparaz, J.S.; Sotomayor Torres, C.M.; Ganguli, S.; Luo, T.
Highlights: The annealing process has a large impact on the thermoelectric properties. Annealing increases the Seebeck coefficient by a factor of as much as 3. Thermal conductivity has a similar trend to reported polycrystalline SnSe. XRD revealed a texture orientation of the grains after annealing processes. Abstract: Tin Selenide (SnSe), a thermoelectric material of the chalcogenide family, has attracted tremendous interest in the past few years due to its unprecedented thermoelectric figure-of-merit, ZT, of 2.6. In this work we have carried out an experimental study of the impact of annealing on the thermoelectric properties of polycrystalline SnSe formed by cold-pressing un-doped SnSe powders with a Hall carrier concentration of 5.37 × 10 17  cm −3 . The crystalline structure and morphology of the samples are characterized and properties, including electrical conductivity, Seebeck coefficient and thermal conductivity, are measured. It is found that thermal annealing has a large impact on both the microstructure and the thermoelectric properties. Notably, annealing leads to re-alignment of crystalline domains, increase in Seebeck coefficient by a factor of as much as 3, and increase in the electrical conductivity. A peak ZT of 0.11 was achieved at 772 K which is smaller than un-doped polycrystalline SnSe.